Association of MTHFR polymorphisms and chromosomal abnormalities in leukemia - Thivaratana Sinthuwiwat (2018)
Genetic variation in MTHFR gene might explain the interindividual differences in the reduction of DNA repaired and the increase of chromosome breakage and damage. Nowadays, chromosomal rearrangement is recognized as a major cause of lymphoid malignancies. In addition, the association of MTHFR polymorphisms with aneuploidy was found in several studies, making the MTHFR gene as a good candidate for leukemia etiology. Therefore, in this study, we investigated the common sequence variation, 677C > T and 1298A > C in the MTHFR gene of 350 fixed cell specimens archived after chromosome analysis. The distribution of the MTHFR polymorphisms frequency was compared in leukemic patients with structural chromosome abnormality and chromosome aneuploidy, as well as in those with no evidence of chromosome abnormalities. We observed a significant decrease in the distribution of T allele in 677C > T polymorphisms among patients with chromosomal abnormalities including both structural aberration and aneuploidy. The same significance result also found in patients with structural aberration when compare with the normal karyotype patients. Suggesting that polymorphism in the MTHFR gene was involved in chromosome abnormalities of leukemia. However, further investigation on the correlation with the specific types of chromosomal aberrations is needed. © 2012 IOS Press and the authors. All rights reserved.